2016
DOI: 10.1002/jhet.2649
|View full text |Cite
|
Sign up to set email alerts
|

New Heterocyclic Compounds Derived from 4,6‐Diamino‐3‐cyano‐2‐methylthiopyridine and their Biological Activity

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Treatment of 4,6-diamino-3-cyano-2-methylthiopyridine (1) with aqueous KOH or hydrazine hydrate afforded the corresponding nicotinamide 2 and pyrazolo[3,4-b]pyridine 3, respectively. Reaction of compound 1 with bromine, sulfuryl chloride, formaldehyde, or aromatic diazonium salts gave 5bromopyridine 4, 5-chloropyridine 5, dipyridylmethane 6, and azo dyes 7-10, respectively. Compound 1 reacted with diketones to yield the corresponding butenylamino derivative 11 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In view of these findings and in continuation of our previous work [20][21][22][23][24][25], we reported herein a simple, rapid, and high-yielding multicomponent reaction protocol for the synthesis of 2-tosyloxyphenylpyridine derivatives 5 and 8-17.…”
Section: Introductionmentioning
confidence: 58%
“…In view of these findings and in continuation of our previous work [20][21][22][23][24][25], we reported herein a simple, rapid, and high-yielding multicomponent reaction protocol for the synthesis of 2-tosyloxyphenylpyridine derivatives 5 and 8-17.…”
Section: Introductionmentioning
confidence: 58%
“…The 160-163 were tested as anti-inflammatory agents. [85] During in vivo studies (using carrageenan paw oedema) in rats these compounds were found efficient oedema inhibitors. Available standards indomethacin and celecoxib both showed 31 % inhibition in 1 h and it increased to more than 60 % after 3 h. The initial results of tested compounds after 1 h were very close to the standard and these compounds exhibited inhibition in the range 30-37 %, while after 3 h the said inhibition was observed in the range 43-64 %.…”
Section: Antiinflamatory and Analgesics Activitiesmentioning
confidence: 99%
“…Recently, quinazoline compounds and the other heterocyclic compounds attracted many scientists due to their various uses and bioactivities such as antiviral activities, anticancer, antitumor, antidiabetic, antiplasmodium, antiparasite, antioxidant, antimicrobial, anti-inflammatory, and antitubercular. Notable examples of quinazoline-based drugs include gefitinib and erlotinib, which are tyrosine kinase inhibitors used in the treatment of nonsmall cell lung cancer. These drugs have demonstrated significant efficacy and have revolutionized targeted cancer therapy.…”
Section: Introductionmentioning
confidence: 99%